Nilai-Nilai Kebermaknaan Hidup Emha Ainun Nadjib dalam Buku Spiritual Journey : Pemikiran dan Permenungan Emha Ainun Nadjib - Ahmad Maujuhan Syah (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2022)
Often people deny the emptiness of their life by uploading a lot of photos or videos that show a sense of happiness in their lives. But it turns out that many have deep sorrow or sadness. This is what ultimately makes human life empty and meaningless. The meaning of life is the human meaning of everything that happens to him. This meaning can be obtained with the depth of the spirituality of humans. Spirituality is belief in relation to the Almighty and also the Creator, for example someone who believes in Allah as the Creator or as the Almighty. Spiritual means the relationship between humans and their God by using mediums such as prayer, fasting, zakat, hajj, prayer, sholawat, and so on. One of the religious and cultural figures with a large number of congregations is Emha Ainun Najib or who is familiarly called Cak Nun. This interfaith figure has traveled to various corners of Indonesia, even abroad. Cak Nun's thoughts have been written in various media. Some have even been recorded, including Democracy La Roiba Fih, Homeless in His Own Village, God Is Fasting, and many others. His writings are the fruit of reflections about himself and his country. The opinions taken are also opinions that are relevant to the life of the lower class. Not grandiose, down to earth and can be accepted by all circles.